Experimental studies on a miniature loop heat pipe with flat evaporator with various working fluids. (5th November 2018) - Anand, A.R.; Jaiswal, Akhil; Ambirajan, Amrit; Dutta, Pradip
Highlights: This paper presents experimental results on a mini-LHP with various working fluids. N-pentane has the lowest temperatures; methanol has the highest heat transport range. It is found that operating temperature follows a vapour figure of merit. Visualization reveals that there is no bubble formation prior to deprime. Deprime is accompanied with intense nucleation inside the CC. Abstract: The goal of this paper is to experimentally study the thermal behavior of a miniature loop heat pipe (LHP) with flat evaporator and correlate the findings with visualization studies of the working fluid within the compensation chamber (CC). A miniature LHP with flat evaporator was fabricated and tested with four working fluids – acetone, methanol, n-pentane and ethanol for various heat inputs till deprime at two different sink temperatures. The CC of the LHP is provided with a glass view port for visualization of the working fluid using a high speed camera. The results show that among the fluids tested, n-pentane has the lowest operating temperature, whereas methanol has the broadest heat load range. Visualization studies with all the four fluids at both sink temperatures reveal that there is no bubble generation in the CC for any heat input level prior to deprime. It was also observed that during deprime, there is explosive nucleation in the CC due to intense heat leak into it, accompanied by a rapid rise in the operating temperature due to cessation of fluid flow in the loop.